Model Kinerja Selling-in (Studi: Outlet Yang Menjual Produk Kalbe Farma OTC di Semarang) - Camilus Isidorus Ikut; Rochdita Yuningsih (Serat Acitya, 2020)
A good marketing performance demonstrate a high level of sales, increasing the number of sales both in units of the product as well as in monetary units. The improved marketing performance also marked by good sales growth from year to year and a higher growth than similar competitors and has a broad customer compared to previous years. This study aimed to analyze the influence of strategy and service outlets and outlet connection with the performance of the selling-in and its impact on the performance of marketingThis study using multiple linear regression analysis using SPSS. The population is all outlets selling OTC product Kalbe diSemarang where the amount is not known for certain. The sample used as many as 100 people with engineering sample selection of non-probability sampling using accidental samplingThe results showed that the strategy and service outlets on the performance of selling in, Relationships outlet affect the performance of selling in, strategy and service outlets on the performance marketing, relations outlets affect the performance of selling in, Performance selling-in effect on the performance of marketing, Strategy service outlets and outlet connection directly affect the performance of marketing through selling performance-insKeywords: Service Strategy Outlet, Relationships Outlet, Performance in Selling, Marketing Performance